INTEGRATING RELIGIOUS TRADITIONS WITHIN THE FRAMEWORK OF SCIENTIFIC PROGRESS AND MODERNITY - Dr. Ismail Adaramola Abdul Azeez; Muhammad Afifuddin (Rihlah Review: Jurnal Pendidikan Islam, 2024)
The debate about the relationship of Islam with modernity has attracted the attention of Islamic scholars. This led to a split into two camps. Pro-modernity circles represented by Islamic Reformist groups can accept modernity and fully support the concept of modernity for the advancement of Islamic civilization. Meanwhile, Islamic circles that are opposed to modernity represented by Islamic revivalist groups reject the existence of modernity because it can threaten Islamic traditions. The rejection of Muslim revivalist is based on the phenomenon of modernity which is very far from Islamic values that rely on traditions made by their clerical figures. This failure to understand modernity arises because they are too fanatical about the Islamic tradition and do not want to read and compromise with the reality and phenomenon of the times, causing a failure to understand the term modernity. This research will explain the debate of Islamic world relations around modernity sourced from Western media that has changed the face of civilization in the Islamic world. The research method used in writing this article is descriptive-qualitative from library research with data sources in the form of books, journals, and online media, as well as other reference materials relevant to the problem studied. The results show that the Islamic world can hardly avoid and stem the incursion of Western media that is so heavily flooding the Muslim world. One can fully access any phenomenon of modernity. This reality has not deterred Muslim intellectuals who are against modernity from trying to maintain the spiritual identity of Islam even though other Muslim world intellectual groups accept modernity by filtering its negative effects. This study will further analyze the challenges of the Islamic world, in addressing modernity.